KUTA BEACH AREA, BALI: A STUDY ON TOURISM ZONING AND CARRYING CAPACITY - I Ketut Astawa; Made Suardani; Anak Agung Putri Suardani (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
Kuta Village is located at Badung regency of Bali province. Its white-sandy beach, good wave and beautiful sunset have attracted tourists to come to Kuta repeatedly. This area is a tourist destination and has become a mainstay tourist attraction of the island of Bali since the early 1970s. Changes in business areas is dynamic and unpredictable. The aim of this study is to explore the form of zoning and carrying capacity of tourism business in Kuta beach area based on current situation and level of the tourism business from the perspective of zoning quality and carrying capacity. The population of this study are tourists and beach vendors in Kuta beach area. The number of population is not known with certainty so to determine the representation of the sample members, determined based on the technique of non-probability sampling that is a purposive sampling technique. Types of data used are quantitative and qualitative data. Data analysed with descriptive statistic and descriptive qualitative approach. The results of this research are 20 business zones and three carrying capacity forms that are relevant to sustainable tourism paradigm consisting of physical carrying capacity, economic carrying capacity and social carrying capacity